AVALIAÇÃO DA QUALIDADE DA MATA CILIAR DE BACIA HIDROGRÁFICA URBANA: UM ESTUDO EM JOÃO MONLEVADE (MG) (REMUNOM, 2024)
Urban watersheds are continually subject to anthropogenic interventions that can compromise their quality, hydrological functions and ecosystem services. Their environmental quality can be assessed using various environmental indicators, one of the most widely used being riparian forest or riparian zone, which borders watercourses and acts as a transition area between the terrestrial environment and the river. This area acts as a shelter for flora and fauna, helps regulate the flow of watercourses, mitigates water contamination by chemical pollutants, dampens floods and absorbs nutrients carried by rain, among other functions. Considering the lack of studies related to the environmental quality of the Jacuí Stream Basin in the municipality of João Monlevade (MG) and the vital role played by this vegetation, the aim of this study was to make a qualitative assessment of the riparian forest in this basin by applying the rapid riparian forest assessment protocol (RQI index) proposed by Tanago and Jalon (2011), where values are assigned to parameters such as the condition of the banks, type and state of the vegetation. The scores obtained ranged from 22 to 50 (very bad to bad) and reflect the environmental conditions and degradation processes occurring in the basin studied, such as (total or partial) suppression of riparian forest, replacement of native vegetation with exotic species and erosion processes. In addition, the lack of riparian forest as a protective element for the banks of the Jacuí Stream contributes to recurrent flooding and erosion in the watershed, compromising its environmental quality and the ecosystem services it provides.Keywords: urban rivers; rapid river assessment; environmental indicators, ecosystem services